Kegiatan Penghijauan Sebagai Upaya Pelestarian Lingkungan dan Peduli Alam di Desa Grogol Sidoarjo - Mochammad Idris; Eli Masnawati (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
To deal with the environmental crisis, greening is an environmental conservation strategy. The concept of greening is needed because regional conditions are developing and the function of space is changing for development. Apart from playing an important role in preserving the environment, humans also have a responsibility to exploit environmental wealth for the ecosystem's survival. The Participatory Action Research (PAR) method builds community commitment to reforestation efforts to preserve the environment. The result is that the climate becomes fresher, healthier, and cooler, nature becomes maintained and clean, and people learn more about greening through planting tree seedlings. Reviving natural aesthetics, using trees as air fresheners, and reducing flooding are the goals of this service initiative.